(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In this article issues of regulation of sports contracts in civil law, contractual obligations in the regulation of contracts in civil law, directions of regulation of sports contract relations in civil law are scientifically analyzed. Practical proposals and recommendations have been developed to improve the quality of sports contracts and ensure full compliance with regulations. The results of research and developed scientific proposals and practical recommendations can be used in practice to ensure compliance by the parties in the conclusion of sports contracts in civil law, to have a positive impact on their legal interests and improve the quality of rights and obligations.